Fc gamma receptor IIIb binding of individual antibody proteoforms resolved by affinity chromatography–mass spectrometry. Issue 1 (1st January 2021) - Lippold, Steffen; Knaupp, Alexander; de Ru, Arnoud H.; Tjokrodirijo, Rayman T. N.; van Veelen, Peter A.; van Puijenbroek, Erwin; de Taeye, Steven W.; Reusch, Dietmar; Vidarsson, Gestur; Wuhrer, Manfred; Schlothauer, Tilman; Falck, David
ABSTRACT: The crystallizable fragment (Fc) of immunoglobulin G (IgG) activates key immunological responses by interacting with Fc gamma receptors (FcɣR). FcɣRIIIb contributes to neutrophil activation and is involved in antibody-dependent cellular cytotoxicity (ADCC) and antibody-dependent cellular phagocytosis (ADCP). These processes present important mechanisms-of-actions of therapeutic antibodies. The very low affinity of IgG toward FcɣRIIIb (KD ~ 10 µM) is a technical challenge for interaction studies. Additionally, the interaction is strongly dependent on IgG glycosylation, a major contributor to proteoform heterogeneity. We developed an affinity chromatography–mass spectrometry (AC-MS) assay for analyzing IgG-FcɣRIIIb interactions in a proteoform-resolved manner. This proved to be well suited to study low-affinity interactions. The applicability and selectivity of the method were demonstrated on a panel of nine different IgG monoclonal antibodies (mAbs), including no-affinity, low-affinity and high-affinity Fc-engineered or glycoengineered mAbs. Thereby, we could reproduce reported affinity rankings of different IgG glycosylation features and IgG subclasses. Additional post-translational modifications (IgG1 Met252 oxidation, IgG3 hinge-region O -glycosylation) showed no effect on FcɣRIIIb binding. Interestingly, we observed indications of an effect of the variable domain sequence on the Fc-binding that deserves further attention. Our new AC-MS method is a powerful tool for expanding knowledge on structure–function relationships of the IgG-FcɣRIIIb interaction. Hence, this assay may substantially improve the efficiency of assessing critical quality attributes of therapeutic mAbs with respect to an important aspect of neutrophil activation.